The Motivation and Behavior of Socialized Reading Users from the Perspective of Mimicry Theory: Taking Wechat Reading as an Example - Li, Yazheng; Zhang, Lezi; Shi, Meng (Advances in Social Sciences Research Journal, 2023)
Thanks to the rapid development of mobile Internet and information technology, the way of public reading is undergoing profound changes. Social reading based on interaction and sharing has become a new trend in digital reading. In this paper, taking WeChat reading as an example, starting from the perspective of "mimicry theory," the stage setting, foreground performance, script management, drama class maintenance, and other elements of the "mimicry theory" presented by WeChat reading are analyzed, and then explore the self-presentation of WeChat reading users in social reading. Further, we will investigate the communication mechanism behind the rapid development of the social reading platform and the resulting problems.